Exploring the connection between atmosphere models and evolution models of very massive stars - Josiek, Joris; Sander, Andreas A. C.; Bernini Peron, Matheus; Ekström, S.; González i Torà, Gemma; Lefever, Roel; Moens, N.; Ramachandran, Varsha; Schösser, Elisa C. (Astronomy and astrophysics, 2025)
Context: Very massive stars (VMSs) are stars that are born with masses of more than 100 M⊙. Despite their rarity, their dominance in the integrated light of young stellar populations and their strong stellar feedback make them worthwhile objects of study. Their evolution is dominated by mass loss, rather than interior processes, which underlines the significance of an accurate understanding of their atmosphere. Yet, current evolution models are required to make certain assumptions on the atmospheric physics which are fundamentally incompatible with the nature of VMS. Aims: In this work, we aim to understand the physics of VMS atmospheres throughout their evolution by supplementing the structure models with detailed atmosphere models capable of capturing the physics of a radially expanding medium outside of local thermodynamic equilibrium. An important aspect is the computation of atmosphere models reaching into deeper layers of the star, notably including the iron-opacity peak as an important source of radiative driving. From this we investigate the importance of the seemingly arbitrary choice of the lower boundary radius of the atmosphere model. Methods: We used the stellar evolution code GENEC to compute a grid of VMS models at solar metallicity for various masses. This grid implements a new prescription for the mass-loss rate of VMS. We then selected the 150 M⊙ track and computed atmosphere models at 16 snapshots along its main sequence using the stellar atmosphere code PoWR. For each snapshot, we computed two atmosphere models connected to the underlying evolutionary track at different depths (below and above the hot iron bump), sourcing all relevant stellar parameters from the evolutionary track itself. Results: We present two spectroscopic evolutionary sequences for the 150 M⊙ track connected to an atmosphere model at different depths. Furthermore, we report on important aspects of the interior structure of the atmosphere from the perspective of atmosphere versus evolution models. Finally, we present a generalized method for the correction of the effective temperature in evolution models and compare it with results from our atmosphere models. Conclusions: The different choice of connection between structure and atmosphere models has a severe influence on the predicted spectral appearance, which constitutes a previously unexplored source of uncertainty in quantitative spectroscopy. The simplified atmosphere treatment of current stellar structure codes likely leads to an overestimation of the spatial extension of VMSs, caused by opacity-induced subsurface inflation. This inflation does not occur in our deep atmosphere models, resulting in a discrepancy in predicted effective temperatures of up to 20 kK. Future improvements with turbulence and dynamically consistent models may resolve these discrepancies.
Gesehen am 29.10.2025